TMIC-08. CHD7 IS SUPPRESSED IN THE PERINECROTIC/ISCHEMIC MICROENVIRONMENT AND IS A NOVEL REGULATOR OF ANGIOGENESIS. (5th November 2018) - Boyd, Nathaniel; Ayokanmbi, Adetokunbo; Walker, Kiera; Whetsel, Julia; Gordillo, Juan; Smith, Cynthia; Gordon, Emily; Herting, Cameron; Hambardzumyan, Dolores; Gillespie, Yancey; Hackney, James; Cooper, Sara; et al.
Abstract: A pathologic hallmark of glioblastoma (GBM), the most common and deadly primary brain tumor in adults, is pseudopalisading necrotic regions in which ischemic conditions are found. Ischemic microenvironments characterized by low oxygen, restricted glucose, and acidic pH due to poor blood supply occurs in both solid tumors and non-neoplastic tissue injury. Modeling these physiologically relevant ischemic conditions within glioblastoma in vitro, we identified chromodomain helicase DNA binding protein 7 (CHD7) as a novel ischemia-regulated gene. CHD7 is an epigenetic reader that controls neural stem cell maintenance and is mutated in CHARGE syndrome, a developmental disorder associated with cranial nerve abnormalities. CHD7 mRNA expression was consistently suppressed in multiple patient-derived xenograft brain tumor lines in response to ischemic conditions, and lower expression of CHD7 correlates with poor GBM patient survival. These microenvironment-mediated decreases in CHD7 protein and mRNA levels observed in glioblastoma were also mirrored in neural progenitor cells in vitro, and CHD7 levels were reduced in the perinecrotic niche of GBM patient and xenograft tissue sections. Genetic targeting of CHD7 increased angiogenesis in vitro in association with differential regulation of angiogenesis associated genes as determined in RNA sequencing analysis. Although targeting CHD7 in orthotopically implanted xenograft brain tumor models did not affect survival outcomes in mice, we observed marked differences in blood vessel architecture and organization, suggesting a major role for CHD7 in regulating vessel formation within these tumors. Together, our data provide insight into the molecular responses to ischemia that regulate angiogenesis.